Feeding and nutrition approaches in Elementary School subjects: a systematic literature review (Research, Society and Development, 2018)
Food is fundamental in the life of the human, and the adoption of healthy eating habits is determinant for their quality of life. Food and nutrition education is inserted in the transversal theme Health of the National Curricular Parameters, being common in Elementary School activities related to the subject in the discipline of Sciences. However, because it’s na easy approach because it’s part of everyone’s daily life, it could and should be worked on in other disciplines as well. Faced with this reality, the following question arises: How have Food and Nutrition been approached in Elementary School, except in the discipline of Science? Thus, the present systematic review aims to analyze the productions in Portuguese that approach the subject in the other disciplines, published in the Portal of Periodical of CAPES, the Bank of Theses and Dissertations of CAPES and in journals of the área of Education with qualis restricted (A1, A2 and B1). The results shows little use of the subject, of 3.845 papers, only nine were related to this theme, being present mainly in interdisciplinary projects. It’s suggested that the teachers of the different disciplines of Middle School insert nutrition education activities in their classes, since their approach in the school context is of great relevance for the promotion of healthy eating from the first years of life.